Analisis Persepsi Generasi Z terhadap Peluang dan Tantangan MLM Syariah Digital - Yunita Ria Anjani; Cintia Putri Prayogha; Syaeful Bahri (Student Scientific Creativity Journal, 2026)
The development of digital technology has encouraged the emergence of various business innovations, including Digital Sharia Multi-Level Marketing (MLM), which combines technological utilization with Islamic economic principles. Generation Z, as a generation closely connected to technology, has significant potential in the development of this business model but also tends to be more critical regarding transparency, company credibility, and compliance with Sharia principles. This study aims to analyze Generation Z’s perceptions of the opportunities and challenges of Digital Sharia MLM and examine its implementation from the perspective of fiqh muamalah. This study employs a qualitative method with a library research approach by collecting secondary data from scientific articles, books, and relevant literature, which are analyzed using the content analysis method. The findings indicate that Digital Sharia MLM offers opportunities through easy access, business flexibility, and technology-based market expansion. However, challenges such as negative perceptions of MLM, potential system deviations, and the need for transparency and adherence to Sharia principles remain major concerns. From the perspective of fiqh muamalah, Digital Sharia MLM is considered permissible as long as it fulfills the principles of halal products, clear contracts, fairness, and is free from elements of riba, gharar, maysir, and practices that may harm other parties.